MAINTAINING AL-MAUN’S SPIRIT AMID THE NEOLIBERALIZATION OF EDUCATION: A BOURDIEUSIAN ANALYSIS OF THE MUHAMMADIYAH MODERN ISLAMIC SCHOOL IN YOGYAKARTA, INDONESIA - Mochamad Iqbal Jatmiko; Hilman Haris Wicaksono; Yesi Mekarsari; Muh. Syukron (JURNAL ILMU SOSIAL, 2025)
This article critically investigates the dual roles of charitable businesses in Muhammadiyah education in Yogyakarta, which reproduce sociocultural, capital, and prestige distinctions among high schools. Beyond prior works focusing on internal dynamics, this study revives the class-based approach to analyze how Muhammadiyah’s education system simultaneously resists and internalizes capitalism’s principles to reconstruct a new field with its logic. Using a qualitative case study with in-depth interviews, we confirm that reproduction models enabling disparity among Muhammadiyah schools are deliberately conducted to sustain philanthropy movements, Al-Maun’s spirit, and program independence amid neoliberal education shifts. The results show that historical context, regulation, and collaborative negotiation legitimize stratified institution quality in which elite schools adopt economic schemes to subsidize non-privileged schools. This dialectic institutionalizes a habitus that rationalizes Muhammadiyah schools’ prestige as socially acceptable. Although causing dominant class concentration, this model becomes a strategy to maintain sovereignty from state/market domination while expanding modern Islamic schools across Indonesia.